Rekonstruksi Pembangunan Hukum Indonesia melalui Pembaruan Asas-Asas Pembentukan Peraturan Perundang-Undangan (Analisis Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 dalam Perspektif Hukum Responsif) - Imam Asmarudin; Erwin Aditya Pratama; Mukhidin (Diktum: Jurnal Ilmu Hukum, 2025)
This study examines the urgency of reconstructing the principles governing legislative drafting in Indonesia in light of the Constitutional Court’s formal review of the Job Creation Law, particularly concerning the omnibus law model. The research addresses two central issues: (1) the implications of the Constitutional Court’s formal review decision for the legislative drafting process; and (2) whether the principles stipulated in Article 5 of Law No. 12 of 2011 on Law-Making are adequate to ensure legal certainty within Indonesia’s dynamic legislative framework. This research employs a normative juridical method, utilizing statutory and conceptual approaches, and is analyzed through a prescriptive legal framework. The findings indicate that the high frequency of judicial review, the phenomena of overregulation, regulatory overlap, and normative disharmony reflect the absence of anticipatory and responsive dimensions in the legislative process. The Constitutional Court’s decision, including the presence of dissenting opinions, underscores the necessity of more adaptive procedural standards capable of responding to evolving legal and societal demands. This study proposes the reconstruction of Article 5 of Law No. 12 of 2011 by incorporating anticipatory and responsive principles as normative instruments to enhance legislative quality and strengthen legal certainty. The scholarly contribution of this research lies in the conceptual formulation of integrating anticipatory and responsive principles into the framework of national legal development.